Las macro destrezas de lenguaje y literatura y la cosmovisión andina en el segundo año del Centro Educativo Comunitario Intercultural Bilingüe de Educación Básica “Silvia Guevara Pérez” de la comunidad Pull Grande cantón Guamote provincia Chimborazo periodo 2019- 2020. - Heredia Bonilla, María José (2020)
The present final report of the Educational Intervention project carried out at the "Silvia Guevara Pérez" Intercultural Bilingual Community Educational Center of the Palmira parish, Guamote canton, Chimborazo province, during the 2019-2020 school year was developed with the objective of implementing methodological strategies in the area of Language and Literature with the intention of improving teaching performance and understanding of the development of macro language skills in children of the Second Year of Basic Education; taking into account their culture and the environment in which they live. The diagnostic tests were applied to 24 students of the Second Year of Basic Education, which were processed and tabulated where difficulties in the skills of listening, speaking, reading and writing were found. Subsequently, the classroom observation was carried out, in which showed that the teachers didn’t stimulate the macro skills of the language when they were teaching in the class. After having tabulated and identified students’ difficulties; the method of orality was applied that consists of creating and developing opportunities where students have a better learning background in a flexible atmosphere focused on their cultural environment, respecting their identity and strengthening the Andean Worldview and promoting the development of macro skills in the area of Language and Literature. Results that benefit the entire educational community were obtained because students achieved the optimum development in the macro skills of the Language, an understanding and appreciation of their Cosmo vision process in which it strengthens their identity, culture and the Learning strategies in teachers.